28. [tex]\sqrt{x}=u=>du=\frac{dx}{2\sqrt{x}}=\frac{dx}{2u}<=>dx=2udu=>\int_{0}^{4}f'(\sqrt{x})dx=\int_{0}^{2}2uf'(u)du=2u.f(u)\left.\begin{matrix} 2\\ 0 \end{matrix}\right|-2\int_{0}^{2}f(u)du[/tex]
36. [tex]\int ln(9-x^2)dx=\int ln(3-x)dx+\int ln(3+x)dx[/tex]
ta có các nguyên hàm sau: [tex]\int lnxdx=x.lnx-x+C[/tex]
áp dụng cho bài trên: [tex]\int ln(3-x)dx=-\int ln(3-x)d(3-x) =-(3-x)ln(3-x)+(3-x)+C;\int ln(3+x)dx=\int ln(3+x)d(3+x)=(3+x)ln(3+x)-(3+x)+C[/tex]
37. bạn làm y như câu 28, đặt 2x=u nha.
bạn thế só vào tính từng câu nha